(untitled) (Journal of the College of Education for Women, 2019)
Passes the Arab order moment political precision of disruption and discord anddifferences of countless between its components and its parts because of the suffering heendured and the suffering now from internal disturbances as a result of lack of cohesionrelations intra-and cultural, historical and lack of interaction between these components sothat became the focus of the policies and interests is an unprecedented degree , reduced withthe joint Arab action to the minimum, and began to focus on the interests of specialregulations.This is with regard suffering internally, but externally the regime Arab Regional is absent thebiggest influence on international decisions because of the courtesies which were carried outat the expense of causes, which came courtesy and concessions as a result of being under fullcontrol of regional powers and international organizations of the United States of Americaand before the United Kingdom and its allies., the Arab system, both regional and internal mobility is witnessing a large andimpressive, and as a result of internal pressure and external, and many of the challenges andrapid changes, which revealed the failure of Arab regimes in the management of politicalcrises of internal and external. On the other hand all the Arab people’s ambition and hope thatthe rise Arab regional system to a level that achieves the self-Arab, away from all selfinterest,personal, and this requires hard work and fixed a bug within the system and within the governing same absent democracy and human rights, and what happened in Tunisia sisterof the projection of the regime, and was followed in Egypt, and the reaction of the Arabmasses in most of the precincts is nothing but a clear and strong will to abandon the Libyanpolitical system, if it amounts to a roiling torrent.